2003
DOI: 10.1023/a:1025900112600
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: FSH values can serve as a predictive factor for the recovery of motile spermatozoa using biopsy in azoospermic patients. On the other hand, histological analysis and other hormone values were not helpful in the prediction of motile sperm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
2
1
0
1
Order By: Relevance
“…Our analysis to assess if cryptozoospermia could be used as a surrogate for hypospermatogenesis histopathology did not, however, reach statistical significance. Our study found that an unsuccessful mTESE was associated with serum testosterone < 300 ng/dL, elevated FSH and Sertoli-cell-only histology, which is consistent with other studies [31,32,34,35].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our analysis to assess if cryptozoospermia could be used as a surrogate for hypospermatogenesis histopathology did not, however, reach statistical significance. Our study found that an unsuccessful mTESE was associated with serum testosterone < 300 ng/dL, elevated FSH and Sertoli-cell-only histology, which is consistent with other studies [31,32,34,35].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies examining patients with non-obstructive azoospermia have identified an association between pre-operative elevated FSH levels and Sertoli-cell-only histology in testicular biopsy following mTESE [31][32][33][34][35]. We found that a significant proportion of patients with cryptozoospermia had a final histopathology consistent with hypospermatogenesis.…”
Section: Discussionsupporting
confidence: 51%
“…Similarly, Souza et al . 28 found that FSH levels can serve as a predictor for motile sperm recovery using biopsy in NOA patients, in which FSH levels <16.05 IU l −1 were significantly associated with the finding of motile spermatozoa ( P < 0.05). In contrast, a study by Ramasamy et al .…”
Section: Discussionmentioning
confidence: 91%
“…[6] Başka bir çalışmada ise FSH <17 olması sperm elde başarısı için prediktif bir faktör olduğu gösterilmiştir. [19] Sonuç olarak NOA hastalarda mTESE ile neredeyse hastaların yarısında sperm elde edilebilmektedir. Testis hacmi, FSH seviyesi ve testisküler histopatoloji TESE başarısını etkileyen faktörler olarak görülmektedir.…”
Section: İstatistikunclassified